Internet banking in Singapore. - Lee, Ling Ling. (2008)
This report traces and examines the current trends of Internet Banking through the SWOT analysis. The main objective of this paper is to propose recommendations to banks, governments and educational institutions that can help to strengthen the foundation of Internet Banking in Singapore. Special attention is paid on how Internet Banking will continue to evolve with the recent developments in wireless technology.